Cost‐Effectiveness of Diet and Exercise for Overweight and Obese Patients With Knee Osteoarthritis. Issue 7 (27th June 2019) - Losina, Elena; Smith, Karen C.; Paltiel, A. David; Collins, Jamie E.; Suter, Lisa G.; Hunter, David J.; Katz, Jeffrey N.; Messier, Stephen P.
Abstract : Objective: The Intensive Diet and Exercise for Arthritis (IDEA) trial showed that an intensive diet and exercise (D+E) program led to a mean 10.6‐kg weight reduction and 51% pain reduction in patients with knee osteoarthritis (OA). The aim of the current study was to investigate the cost‐effectiveness of adding this D+E program to treatment in overweight and obese (body mass index >27 kg/m 2 ) patients with knee OA. Methods: We used the Osteoarthritis Policy Model to estimate quality‐adjusted life‐years (QALYs) and lifetime costs for overweight and obese patients with knee OA, with and without the D+E program. We evaluated cost‐effectiveness with the incremental cost‐effectiveness ratio (ICER), a ratio of the differences in lifetime cost and QALYs between treatment strategies. We considered 3 cost‐effectiveness thresholds: 50, 000/QALY, 100, 000/QALY, and 200, 000/QALY. Analyses were conducted from health care sector and societal perspectives and used a lifetime horizon. Costs and QALYs were discounted at 3% per year. D+E characteristics were derived from the IDEA trial. Deterministic and probabilistic sensitivity analyses (PSAs) were used to evaluate parameter uncertainty and the effect of extending the duration of the D+E program. Results: In the base case, D+E led to 0.054 QALYs gained per person and cost 1, 845 from the health care sector perspective and 1, 624 from the societal perspective. This resulted in ICERs of 34, 100/QALY and 30, 000/QALY. In the health care sector perspective PSA, D+E had 58% and 100% likelihoods of being cost‐effective with thresholds of 50, 000/QALY and 100, 000/QALY, respectively. Conclusion: Adding D+E to usual care for overweight and obese patients with knee OA is cost‐effective and should be implemented in clinical practice.